Economic Aspects of Minimum Quantity Lubrication (MQL) in Milling of Magnesium Alloy - Kamil P. WASZCZUK; Rafal FENC (Communications of International Proceedings, 2025)
This paper examines the applicability of minimum quantity lubrication (MQL) in the milling of magnesium alloys. The experimental procedure involved the progressive introduction of additional MQL nozzles to assess the influence of the aerosol on surface roughness and production costs. The results indicate that increasing the number of dosing nozzles does not yield a significant improvement in surface quality, while it markedly increases manufacturing costs. Furthermore, it was observed that dry machining, conducted without any coolant, leads to higher surface roughness values. These findings support the application of MQL in the milling of magnesium alloys as an effective compromise between surface quality and economic efficiency.
Keywords: cost of the process; MQL; magnesium alloys; roughness surface